2014
DOI: 10.1016/j.stemcr.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Traceable and Transplantable Photoreceptors from Mouse Embryonic Stem Cells

Abstract: SummaryRetinal degenerative diseases resulting in the loss of photoreceptors are one of the major causes of blindness. Photoreceptor replacement therapy is a promising treatment because the transplantation of retina-derived photoreceptors can be applied now to different murine retinopathies to restore visual function. To have an unlimited source of photoreceptors, we derived a transgenic embryonic stem cell (ESC) line in which the Crx-GFP transgene is expressed in photoreceptors and assessed the capacity of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
106
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 45 publications
9
106
0
1
Order By: Relevance
“…The biological capacity of the former-mentioned cells resembles that of freshly dissociated Nrl-GFP-positive photoreceptor precursors collected from postnatal day 4 retinas. This age corresponds to the best photoreceptor differentiation stage for transplantation [5,6].In close agreement with Gonzalez-Cordero's work, the transplantation of early-born photoreceptors generated from an ES cell line expressing GFP under the control of the Crx specific photoreceptor promoter gives similar results [66,68]. This study generated a fine-tuned 3D culture system to track developing photoreceptors in the dish.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The biological capacity of the former-mentioned cells resembles that of freshly dissociated Nrl-GFP-positive photoreceptor precursors collected from postnatal day 4 retinas. This age corresponds to the best photoreceptor differentiation stage for transplantation [5,6].In close agreement with Gonzalez-Cordero's work, the transplantation of early-born photoreceptors generated from an ES cell line expressing GFP under the control of the Crx specific photoreceptor promoter gives similar results [66,68]. This study generated a fine-tuned 3D culture system to track developing photoreceptors in the dish.…”
supporting
confidence: 86%
“…In both studies the number of integrated cells is similar and the photoreceptors undergo a full maturation with the formation of long outer segment containing proteins of the photo transduction pathway as well as specific proteins necessary for the outer segments structure. The inverse translocation movement of Arrestin and Transducin (GNAT1) under light exposure reveals that the transplanted cells have a certain capacity to respond to light stimuli [66]. Interestingly, in both studies, the transplanted photoreceptors form synapses with the adjacent bipolar cells.…”
mentioning
confidence: 96%
“…The Sasai group demonstrated that dissociated mESC reaggregate to form embryoid bodies in a 96-well low adhesion plate and form optic vesicles after addition of 2% Matrigel; when then cultured in suspension, they give rise to clearly recognizable retinal layers containing all the major retinal cell types as in vivo. 52 Importantly, rod photoreceptor precursors obtained from mESC with this protocol were able to integrate and mature in the adult degenerate retina, 116,117 contrary to what had been observed with a 2D retinal differentiation protocol. 114 Using this new advanced 3D protocol, derived rod precursors transplanted in a degenerate adult retina successfully formed inner and outer segments, which were correctly orientated toward the RPE of the host retina.…”
Section: Generating Transplantation-competent Photoreceptors: Lessonsmentioning
confidence: 81%
“…However, these structures develop at low efficiency and their successful dissection is what determines the retinal organoid yield, which can be quite limited. Emitting dissection risks compromising the retinal identity of organoids with integration of non-retinal structures (81,82). Völkner et al provide a protocol for unbiased neuroepithelium trisection at the eyefield stage to produce high numbers of large, stratified organoids committed to retinal fate (79).…”
Section: Three-dimensional Organoidsmentioning
confidence: 99%